Understanding the relationship between poverty and inequality: overview report - Bucelli, Irene (2019)
An understanding that poverty and inequality are inextricably linked has given rise to a number of large international organisations setting joint inequality-poverty reduction targets on the basis that poverty cannot be seriously tackled without addressing inequality. However, the evidence base was relatively weak with only limited information available on the relationship between the two phenomena. The programme was designed to expand the evidence base on the links between inequality and poverty and to fill this knowledge gap. In the research summarised in this report we explored the relationship between inequality and poverty by: • Examining philosophical concerns for poverty and inequality and how they may overlap • Estimating the empirical relationship between income inequality and a variety of poverty measures • Reviewing the existing evidence base on potential mechanisms that may drive any relationshi